Mengejar Pekerjaan Impian: Pelatihan Daring Membuat Curriculum Vitae dan Cover Letter - Eugenius Tintus Reinaldi; Christa Vidia Rana Abimanyu (Universitas Katolik Soegijapranata, 2021)
Freshly graduated students are expected to get a job soon, but the competition in the job-seeking world is getting tougher because the number of fresh-graduate continues to increase from year to year. The first stage of employee selection is administrative selection, which can be done from Curriculum Vitae and Cover Letter sent by applicants. Considering that this first stage is crucial for determining the next stage, CV and CL must be made seriously and with consideration. This training aims to provide provisions in the form of strategies for making CV and CL for students who have just graduated from college. The training was attended by 27 students who are currently taking thesis courses and those who have finished their thesis trial using the online method using cyber.unika.ac.id. The training participants had a positive reaction to this training. In addition, their skills in making CV and CL have also improved, seen from the CV and CL results that were collected by the participants after the training ended.